Policy Option for Agriculuture in Facing The Impact of Sea Level Rise in The South Kalimantan Province - Akhmad R. Saidy; Yusuf Azis (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2010)
-